Choice of the Optimal Solution for Introducing vIMS Technology in the Infrastructure of the Telecommunication Network - Alekseenko A. A., Belov Y. N. (Interactive science, 2020)
the article focuses on the main driving forces that force telecom operators to introduce the latest achievements of scientific and technological progress into their networks and provide subscribers with new opportunities and advantages. One of the latest advances in the world of telecommunications is the IP Multimedia Subsystem (IMS). Based on literary sources, a review of the IMS concept is carried out, the main ideas embodied by it are highlighted. The paper provides a solution for the implementation of virtual IMS technology in the telecommunications network infrastructure, defines the main network equipment on which the functional components of the vIMS network are implemented.
Keywords: концепция; конвергенция; архитектура сети; concept; уровень управления; convergence; network architecture; IP multimedia subsystem; IP multimedia subsystem; vIMS; vIMS; control layer